VD_FINDINFO HC / 2018 / 723 vom 22. August 2018 - VD Tribunal cantonal (2018)
DÉCISION D'IRRECEVABILITÉ, ACTE DE RECOURS, LITISPENDANCE, DÉCISION ÉTRANGÈRE | 27 CL, 59 al. 2 let. d CPC (CH), 64 CPC (CH)